Death and Dying in the Bhagavad-Gita: Between Causality and Soteriology - Petek, Nina (Religions of South Asia, 2018)
The Bhagavad-Gita is one of the most important works in the philosophical-religious tradition of India, which, among other things, offers a complex teaching on death and dying. This article focuses on the four basic characteristics of death, as they appear in the poem: death as a source of selfawareness, death as an element giving meaning to the existence in the social and individual context, death as an aesthetic experience, and death as ritual, meditative performance. In the process, the essential doctrines which support these dimensions of death will be illuminated on the basis of textual analysis with reference to some ideas from the Vedas and the Upanisads: the relationship between the transience of the body and the immortality of the spirit, the teaching on two deaths, phenomenal and unconditional, which is based on the tension between the social and the individual, and the relationship between the fatefulness and the freedom of death which will be presented in the context of the doctrine of time, which emerges from the visual encounter with death as the ‘wholly other’. This is also the source of the aesthetic experience, which, however, leads from death as something entirely different, alien and external to the essential internalization, which culminates in the very moment of death, when all the individual’s profane and soteriological endeavours are measured.